Comparative Study on the Adoption of Improved Beekeeping Technology for Poverty Alleviation - Bhusal, SJ; Thapa, RB (Journal of the Institute of Agriculture and Animal Science, 2005)
Adoption of improved beekeeping practices was compared between the mobilized (Pragatinagar VDC) and non-mobilized (Makar VDC) farmers’ groups (n = 14 in each VDC) of Nawalparasi district using semistructured questionnaire survey after introducing improved beekeeping practices during 2002/2003. Majority of the households (82.4%) from mobilized group practiced beekeeping enterprise of which 80.6% followed improved practices with adoption index of 77.44% while from non-mobilized group only 56.0% adopted beekeeping enterprise and 68.4% followed improved beekeeping practices only with the adoption index of 58.73%. Annual honey yield per colony was significantly higher among mobilized farmers’ group (25.6 kg earning NRs 25,657.14) than that of non-mobilized farmers’ group (15.6 kg earning NRs 10,364.29). Women involvement was low in enterprise development and adoption in both VDCs (31.8% and 50.0% in mobilized VDC; and 35.7% and 48.2% in non-mobilized VDC). Therefore, transfer of improved technology to subsistence farmers emphasizing women through social mobilization could help generate income and alleviate poverty. Key words: Beekeeping, social mobilization, adoption index, gender, income J. Inst. Agric. Anim. Sci. 26:117-125 (2005)